A writer’s resource : - Maimon, Elaine P. (McGraw-Hill, 2002)
Comb-bound and clearly tabbed, A Writerâs Resource combines 20 years of research into writing in college with the most extensive technological support available to form an indispensable resource for learning, writing, researching, and editing.